Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Simplify 4(6 - 2x) - 3(3 - 4x)

4x + 15
15 - 20x
15 - 6x


Sagot :

Answer:

4x+15 Is the answer

Step-by-step explanation:

4(6−2x)−3(3−4x)

Distribute:

=(4)(6)+(4)(−2x)+(−3)(3)+(−3)(−4x)

=24+−8x+−9+12x

Combine Like Terms:

=24+−8x+−9+12x

=(−8x+12x)+(24+−9)

=4x+15

Hey there!

“ Simplify 4(6 - 2x) - 3(3 - 4x)”

FIRST: you have to DISTRIBUTE

4(6) + 4(–2x) + (–3)(3) + (–3)(–4x)

4(6) = 24

4(–2x) = –8x

–3(3) = –9

–3(–4) = 12x

NEW EQUATION: 24 – 8x – 9 + 12x

SECOND: COMBINE your LIKE TERMS

(24 – 9) + (–8x + 12)

24 – 9 = 15

–8x + 12 = 4x

OR........ (MAINLY this one )

(–8x + 12) + (24 - 9)

(–8x + 12) = 4x ⬅️ FRONT NUMBER

24 – 9 = 15 ⬅️ BACK NUMBER

ANSWER: 4x + 15 ☑️

Good luck on your assignment and enjoy your day!

~LoveYourselfFirst:)